Perception of femininity and attractiveness in Facial Feminization Surgery - Ching, Ann Hui (Ann Transl Med, 2021)
BACKGROUND: Facial Feminization Surgery (FFS) alters bone and soft tissue to feminize facial features of transgender females. This study aims to evaluate perceptions of femininity, attractiveness, and ideal surgical outcomes in transgender females, non-transgender females and plastic surgeons. METHODS: The data was extracted from a survey of transgender females (n=104), non-transgender females (n=192) (completion rate of 48.4%) and plastic surgeons who performed FFS (n=23) (survey response rate of 31.5%). Five virtually-modified forms of three facial features, the nasal tip width, supratip break, mandibular gonial angles, and the composite images of the above features of an individual, assigned male at birth, were used. Respondents were requested to select and rank images based on personal perceptions of femininity and attractiveness. RESULTS: Transgender females chose a narrower nasal tip width as more attractive (P≤0.001), and evaluated a more acute supratip angle, and more obtuse mandibular gonial angle as both more feminine and attractive (all P≤0.023) compared to non-transgender females. Plastic surgeons chose a more obtuse mandibular gonial angle as more feminine (P=0.007) and a more ideal surgical outcome (P=0.046), compared to transgender female respondents. In the assessment of composite images, non-transgender female ranked the options with more obtuse mandibular gonial angle as more feminine (all P≤0.036) than transgender females. CONCLUSIONS: Acknowledging the difference in transgender females’ perceptions of facial femininity and attractiveness from non-transgender females and plastic surgeons could assist plastic surgeons in managing expectations of surgical outcomes.